Exploring the Integration of Artificial Intelligence in Vietnamese Tertiary EFL Education: Teacher Perspectives and Pedagogical Challenges - Hua Hong Hieu; Le Thanh Thao; Pham Trut Thuy (Vision: Journal for Language and Foreign Language Learning, 2024)
This qualitative study investigates the concerns of Vietnamese tertiary English as a Foreign Language (EFL) teachers regarding the integration of Artificial Intelligence (AI) in their classrooms. As educational landscapes evolve with technological advancements, understanding educators’ perspectives on AI becomes crucial, especially in settings where technological integration is still emerging. The study involved semi-structured interviews with nine EFL teachers from two Vietnamese institutions, categorized into three career stages: novice, mid-career, and near-end career. This approach provided insights into the varying perceptions and challenges experienced by teachers at different professional phases. The findings revealed four main themes: “Technological Integration Challenges in EFL Classrooms,” highlighting the difficulties in incorporating AI tools into teaching practices; “Pedagogical Concerns and AI’s Impact on Teacher-Student Interaction,” expressing worries about how AI might alter traditional educational dynamics; “Professional Development and Readiness for AI Integration,” emphasizing the need for targeted training; and “Concerns about AI’s Impact on Student Learning Outcomes,” focusing on the effectiveness of AI in enhancing student achievement. These themes suggest a need for comprehensive professional development in AI, careful implementation that considers the human element in education, and adaptable strategies for AI integration across different career stages. This research contributes to the growing discourse on AI in education, highlighting specific challenges and needs in the Vietnamese tertiary EFL context.